PEMBENTUKAN LAPANGAN FAKTOR DARI SUATU DAERAH INTEGRAL - Tri Widjajanti; Dahlia Ramlan; Rium Hilum (Jurnal Natural, 2009)
Ring of integers under the addition and multiplication as integral domain can be imbedded to the field of rational numbers. In this paper we make a construction such that any integral domain can be a field of quotient. The construction contains three steps. First, we define element of field F from elements of integral domain D. Secondly, we show that the binary operations in fare well-defined. Finally, we prove that f : D ® F is an isomorphisma. In this case, the polynomial ring F[x] as the integral domain can be imbedded to the field of quotient..